Boundedness of Some Commutators of Marcinkiewicz Integrals on Hardy Spaces (Analysis in Theory and Applications, 2023)
Based on the results of the boundedness of $μ^b_Ω$ on $L^p$ spaces, by using thetheory of atomic decomposition of Hardy spaces, we obtain the boundedness of $μ^b_Ω$ onHardy spaces.